2010
DOI: 10.1021/am100605a
|View full text |Cite
|
Sign up to set email alerts
|

Sonication-Assisted Synthesis of CdS Quantum-Dot-Sensitized TiO2 Nanotube Arrays with Enhanced Photoelectrochemical and Photocatalytic Activity

Abstract: A sonication-assisted sequential chemical bath deposition (S-CBD) approach is presented to uniformly decorate CdS quantum dots (QDs) on self-organized TiO2 nanotube arrays (TNTAs). This approach avoids the clogging of CdS QDs at the TiO2 nanotube mouth and promotes the deposition of CdS QDs into the nanotubes as well as on the tube walls. The photoelectrochemical and photocatalytic properties of the resulting CdS-decorated TNTAs were explored in detail. In comparison with a classical S-CBD approach, the sonica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
154
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(164 citation statements)
references
References 26 publications
3
154
1
2
Order By: Relevance
“…In addition, most of electrons react with H 2 O 2 molecules in the water to yield abundant hydroxyl radicals • OH to remove RhB molecules. Meanwhile, the holes can also directly degrade RhB molecules [51,52]. It should be pointed out that H 2 O 2 serves as an efficient electron scavenger, which can also facilitate separation and transfer of charge carriers to improve the photocatalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, most of electrons react with H 2 O 2 molecules in the water to yield abundant hydroxyl radicals • OH to remove RhB molecules. Meanwhile, the holes can also directly degrade RhB molecules [51,52]. It should be pointed out that H 2 O 2 serves as an efficient electron scavenger, which can also facilitate separation and transfer of charge carriers to improve the photocatalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…The quantum size effect (QSE) alters the energy levels of the conduction and the valence band edges in the coupled semiconductor systems, which favors the interparticle electron transfer resulting in low carrier recombination rate. Xie et al [49] showed that CdS QDs sensitized TiO 2 nanotubes exhibited high photocatalytic activity towards methyl orange (MO) dye due to the quick charge transfer from CdS to TiO 2 conduction band. Another important work carried out by Wang et al [50] showed clearly the QSE in photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25] Among these tactics, constructing TiO 2 -based heterostructure has been demonstrated effective for improving photocatalytic efficiency through promoting the photogenerated charge separation, harvesting visible light and facilitating CO 2 activation. [26,27] Various types of second-component semiconductor of TiO 2 -based heterostructure have been reported, such as CdS, [28] CeO 2 [29] and ZrO 2 [30] and so on. On this basis, an electron transfer mediator (Pt, [31] Au, [32] and graphene oxide [33][34][35] ) embed in the heterostructure interface can strengthen the interface charge transfer and result in a vectorial electron transfer via a Z-scheme system, [36] which can efficiently improve photogenerated separation and photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%